The Shift in the Husband’s Leadership and Its Consequences to Family Goals - Urfan Hilmi; Idzam Fautanu; Nandang Najmudin; Badri Khaeruman (Jurnal Iman dan Spiritualitas, 2023)
This study aims to understand more deeply the shift in husband's leadership and its negative impact on the family. This qualitative research uses the descriptive analysis method. The approach used is a normative and sociological legal research approach. Data was collected using a literature study technique. Then, the data were analyzed using qualitative data analysis techniques: studying, reducing, correcting, tabulating, categorizing, interpreting, and drawing conclusions. This study found that social changes caused a shift in the husband's leadership, harming the family psychologically and sociologically.